An Adipokinetic Hormone Acts as a Volume Regulator in the Intertidal Gastropod Mollusk, Aplysia californica - Martillotti, Anthony W.; Tsai, Pei-San (Frontiers in Endocrinology, 2018)
Adipokinetic hormone (AKH) is a multifunctional neuropeptide in the gonadotropin-releasing hormone superfamily. In insects, AKH acts to mobilize energy stores during times of high energetic demand, but has been shown to have other effects. In lophotrochozoans, the presence and function of AKH are less characterized. We have previously identified an AKH in an intertidal gastropod mollusk, the California sea hare (Aplysia californica), and named it ac-AKH. Our previous data showed ac-AKH induced an acute weight loss, suggesting a role in volume regulation. The overarching goals of this study were to test the role of ac-AKH as a volume regulator and examine the mechanism by which ac-AKH induced the acute weight loss. Our results showed that ac-AKH reduced body mass, in part, through the reduction of hemolymph volume without altering hemolymph osmolality or specific osmolytes. The effect of ac-AKH on volume loss was accentuated under a hyposaline condition. We further showed that ac-akh expression was inhibited during a hyposaline challenge, and that the administration of ac-AKH partially reversed the increase in body mass, but not hemolymph osmolality change, caused by the hyposaline challenge. These data collectively show that ac-AKH is a proximate regulator controlling the fluid volume, but not osmolality, in A. californica. Importantly, our results highlight the functional divergence of this structurally conserved neuropeptide in the molluscan lineage.